Perceptions of risk and safety within injection settings: Injection drug users' reasons for attending a supervised injecting facility in Vancouver, Canada - Small, W.; Moore, David; Shoveller, J.; Wood, E.; Kerr, T. (Routledge, 2012)
The settings where drugs are injected represent a crucial dimension in the social structural production of drug-related harm. While the use of supervised injecting facilities has been associated with reductions in injection-related risk, few studies have examined the reasons why injection drug users utilise supervised injecting facilities. This study sought to explore injectors’ motivations for injecting within the local supervised injecting facility (Insite) and how the supervised setting interacts with their situated risk perceptions. Fifty in-depth interviews were conducted with injection drug users who utilise Insite (Vancouver, Canada) in order to understand injectors’ reasons for attending the supervised injecting facility and how the injection setting is perceived to influence risk. Participants were drawn from the Scientific Evaluation of Supervised Injecting cohort. Interviewees reported that Insite provides a suitable alternative to other injection settings (e.g. public injecting venues) and negates the need to observe social conventions deemed to be undesirable by some drug users. The facility mediates injection-related health risks by reducing the potential for blood-borne virus infection and overdose. The sanctioned and regulated environment of Insite is also perceived to provide refuge from important forms of ‘everyday risk’, including encounters with police, street violence and loss of drugs, which characterise other injection settings. While public health perspectives have focused upon the potential of supervised injecting facilities to mediate injection-related harm, injection drug users perceive the supervised injection setting to provide protection from a broader range of hazards associated with injecting drugs in unregulated settings.